Latent political engagement: Insights from new measures for local democracy - Tobias Schib; Michael Strebel; Alois Stutzer (University of Basel, Center of Business and Economics (WWZ), 2025)
A functioning democracy relies on individuals motivated to take on political office. In recent decades, concerns have grown across Western democracies about increasing political alienation and a declining willingness among citizens to engage in politics. To systematically assess this phenomenon, we introduce the concept of latent political engagement defined as an underlying, non-specific motivation to take on the responsibilities of a political mandate, whether or not it ultimately results in an actual candidacy. To capture it, we propose four survey questions. We fielded them using a large-scale, nationally representative survey of Swiss citizens in 2023. We present descriptive evidence for differences across various socio-economic groups and contextual factors. In particular, we find that individuals who are deeply invested in their municipality - whether through homeownership (economic capital) or membership in local associations (social capital) - exhibit higher levels of latent political engagement. Moreover, municipality size emerges as a key predictor, with small jurisdictions being particularly conducive to fostering a willingness to take on political mandates. Additionally, we provide evidence of language-cultural differences, as native German-speaking individuals are substantially more likely than French speakers to have ever considered holding political office.
Keywords: D72; J45; 330; Local democracy; political engagement; political ambition; political selection